The Effect of Dribbling Learning In Basketball On Improving The Gross Motor Ability of Children With Might And Mediated Mental Disabilities At SLB Negeri 1 Makassar (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of basketball dribbling learning on improving gross motor skills in children with mild and moderate mental retardation at UPT SLB Negeri 1 Makassar. This study uses a quasi-experimental method with descriptive and inferential data analysis techniques. Based on the results of the descriptive statistical analysis of the Pretest and Posttest, the average value (mean), standard deviation, minimum value, and maximum value for each gross motor aspect increased, while the inferential statistical analysis obtained by the normality test showed that the significance value for each aspect (balance, coordination, movement rhythm, and muscle strength) was above 0.05, so that the data was considered to meet the normality assumption, for the homogeneity test using Levene's Test, the significance value was > 0.05, so that the homogeneity assumption was met. This indicates that the distribution of variance between groups can be considered equal. The paired sample t-test was used to determine whether there was a significant difference between the pretest and posttest scores. The test results showed that all four aspects had a significance value (p-value) < 0.05, which means there was a statistically significant difference between before and after treatment. Based on the calculation of the percentage increase, it was obtained that: Balance increased by 17.6%, Coordination by 28.6%, Movement rhythm by 41.7%, and Muscle strength increased by 11.1%. Therefore, the implementation of effective dribbling training learning provides a meaningful contribution to the development of gross motor skills in children with mild and moderate mental retardation at UPT SLB Negeri 1 Makassar